2020
DOI: 10.1111/os.12708
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Approaches for Accurate Determination of the Quadriceps Angle

Abstract: Objectives A retrospective study was conducted using magnetic resonance image (MRI) and a full‐length standing scanogram (FLSS) to measure the quadriceps angle (Q‐angle) while avoiding soft tissue interference. Methods Two steps were retrospectively carried out in two case series. The first step involved using MRI to define the standardized patellar center (PC) and the tibial tubercle (TT) on the frontal plane of the MRI in one group of 60 consecutive patients (from July 2016 to December 2016, 29 men and 31 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Males had longer lengths in the lateral region of their patellar tendon compared with the medial and central regions, while females did not. This was expected, considering that females have a static knee position with larger knee abduction angle compared with males 26 . Similar results were observed by Yanke et al 10 that found that the lateral region of the patellar tendon is longer than the medial and central regions in a study with male cadavers.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Males had longer lengths in the lateral region of their patellar tendon compared with the medial and central regions, while females did not. This was expected, considering that females have a static knee position with larger knee abduction angle compared with males 26 . Similar results were observed by Yanke et al 10 that found that the lateral region of the patellar tendon is longer than the medial and central regions in a study with male cadavers.…”
Section: Discussionsupporting
confidence: 85%
“…This was expected, considering that females have a static knee position with larger knee abduction angle compared with males. 26 Similar results were observed by Yanke et al 10 that found that the lateral region of the patellar tendon is longer than the medial and central regions in a study with male cadavers. This finding may in part explain the differences in prevalence of patellar tendinopathy between sexes.…”
Section: Discussionsupporting
confidence: 81%
“…Postoperative functional assessment was performed using the Musculoskeletal Tumor Society (MSTS) Functional Scoring System and the Toronto Extremity Salvage Score (TESS) 24,25 . The measurement of the length of the lower limb was conducted via a full‐length standing scanogram 26 …”
Section: Methodsmentioning
confidence: 99%
“…24,25 The measurement of the length of the lower limb was conducted via a full-length standing scanogram. 26…”
Section: Follow-upmentioning
confidence: 99%
“…The causes of PM have been enthusiastically pursued, and three predisposing factors have been advocated: imbalanced peripatellar soft-tissue tension, lower-extremity malalignment, and bone or muscle anomalies ( Table 1 ) [ 17 ]. Among them, the first factor is considered the most important, for which nonsurgical treatment is generally effective.…”
Section: Pathognomonic Mechanism Of Patellar Malalignmentmentioning
confidence: 99%